2000
DOI: 10.1253/jcj.64.745
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Aortic Atherosclerosis and Carotid Atherosclerosis in Coronary Artery Disease

Abstract: The present study investigated the relationship between aortic atherosclerosis and carotid atherosclerosis, and studied the effects of coronary risk factors for these arteries. The subjects consisted of 78 patients with coronary artery disease (CAD) and 69 patients without CAD. All subjects underwent enhanced computed tomography and B-mode ultrasonography within a short time period to determine the extent of aorta and carotid atherosclerosis. Significant correlations between maximal aortic wall thickness (MAWT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 16 publications
0
14
0
1
Order By: Relevance
“…Enhanced computed tomography can visualize atherosclerotic changes in humans, 13 but is difficult to use for mice. Magnetic resonance imaging (MRI) may be a promising technique for assessing the murine heart; 14, 15 Fayad et al reported noninvasive in vivo high-resolution MRI with a high field magnet (9.4 T) of atherosclerotic lesions in apoE-KO mice, 16 but no information was provided about the morphological and functional changes of the thoracic aorta, aortic valve or heart.…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced computed tomography can visualize atherosclerotic changes in humans, 13 but is difficult to use for mice. Magnetic resonance imaging (MRI) may be a promising technique for assessing the murine heart; 14, 15 Fayad et al reported noninvasive in vivo high-resolution MRI with a high field magnet (9.4 T) of atherosclerotic lesions in apoE-KO mice, 16 but no information was provided about the morphological and functional changes of the thoracic aorta, aortic valve or heart.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26] With regard to aortic stiffness, it has been the TG level, not TC or LDL-C levels, that has been associated with decreased common carotid arterial distensibility in healthy non-diabetic middleaged women. 27 Furthermore, previous reports have shown that in patients with familial hypercholesterolemia, severe dyslipidemia can lead to impairment of the elastic properties of the aorta before the clinical manifestation of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…The IMT of the carotid, aortic, femoral and brachial arteries were significantly higher in patients with CAD compared with controls, [41][42][43] and moreover, the IMT of the common carotid artery is increased in older subjects with asymptomatic myocardial ischemia as evidenced by exercise ECG alone or in combination with thallium scan. Thus, it has been suggested that carotid US may help to identify asymptomatic individuals with CAD.…”
Section: Predictor Of Cadmentioning
confidence: 92%